Bentuk Pertunjukan Tari Tradisional Penginang Penampi di Kabupaten Lombok Tengah Nusa Tenggara Barat - -, Baiq Larre Ginggit Sekar Wangi; Rapi Renda; I Wayan Kusuma Di Biagi (Universitas Hamzanwadi, 2024)
This study aims to explain and analyze the form of the Penginang Penampi dance performance in the process of inheriting traditional dances of the Central Lombok Regency, West Nusa Tenggara. This study uses a qualitative descriptive method with an interdisciplinary approach. Research data with three data collection techniques, namely observation, interviews, and documentation. Data validation is carried out by means of reflection, peer opinion, and rational analysis. The data analysis technique uses data triangulation techniques. The flow of data analysis techniques used is the interactive model analysis flow starting from data collection, data reduction, data presentation and data verification. The results of the study show the following findings: the form of the Penginang Penampi dance performance in Central Lombok Regency, West Nusa Tenggara is the Penginang Penampi dance movement, the main movement is the initial movement, the core movement and the closing movement. The theme of the Penginang Penampi dance includes non-dramatic dance (traditional dance). the accompanying music uses gamelan gendang beleq, the costume uses the Sasak tribe's clothing, namely the